Glucose upshift of carbon-starved marine Vibrio sp. strain S14 causes amino acid starvation and induction of the stringent response - Flardh, K.; Kjelleberg, S. (Journal of Bacteriology, 1994)
The physiological status of carbon-starved cells of the marine Vibrio sp. strain S14 has been investigated by the analysis of their immediate response to carbon and energy sources. During the first minute after glucose addition to 48-h-starved cells, the pools of ATP and GTP increased rapidly, and the [ATP]/[ADP] ratio reached the level typical for growing cells within 4 min. The total rates of RNA and protein synthesis increased initially but were inhibited 4 to 5 min after glucose addition by the induction of the stringent response. A mutation in the relA gene abolished stringent control during the recovery and significantly prolonged the lag phase, before the starved cells regrew, after the addition of a single source of carbon. However, both the wild-type and the relA cells regrew without a significant lag phase when given glucose supplemented with amino acids. On the basis of these results, it is suggested that carbon-starved cells are deficient in amino acid biosynthesis and that ppGpp and the stringent response are involved in overcoming this deficiency, presumably by derepressing the synthesis of amino acid biosynthetic enzymes. Furthermore, the data suggest that the starved cells primarily are starved for energy, and evidence is presented that the step-up in the rate of protein synthesis after refeeding is partially dependent on de novo RNA synthesis.